2011
DOI: 10.1007/s13595-011-0039-5
|View full text |Cite
|
Sign up to set email alerts
|

Effects of shrub and canopy cover on the relative growth rate of Pinus pinaster Ait. seedlings of different sizes

Abstract: International audienc

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
33
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 32 publications
2
33
0
2
Order By: Relevance
“…One of the main abiotic factors limiting natural establishment of woody species in the Mediterranean region and in other Mediterranean ecosystems is summer drought (see Castro et al (2004a) and references inside). Several studies have indicated that pioneer shrubs can facilitate tree seedling survival and growth during natural establishment in Mediterranean forest communities, acting as nurse shrubs (Callaway, 1992;Castro et al, 2004b;Gómez-Aparicio et al, 2005b;Rodríguez-García et al, 2010;Rodríguez-García et al, 2011). This leads us to think that facilitation might be a common process in Mediterranean plant communities at early stages and in moisture-limited environments, which agrees with the theory of the stress-facilitation relationship described by Bertness and Callaway (1994).…”
Section: Introductionsupporting
confidence: 83%
“…One of the main abiotic factors limiting natural establishment of woody species in the Mediterranean region and in other Mediterranean ecosystems is summer drought (see Castro et al (2004a) and references inside). Several studies have indicated that pioneer shrubs can facilitate tree seedling survival and growth during natural establishment in Mediterranean forest communities, acting as nurse shrubs (Callaway, 1992;Castro et al, 2004b;Gómez-Aparicio et al, 2005b;Rodríguez-García et al, 2010;Rodríguez-García et al, 2011). This leads us to think that facilitation might be a common process in Mediterranean plant communities at early stages and in moisture-limited environments, which agrees with the theory of the stress-facilitation relationship described by Bertness and Callaway (1994).…”
Section: Introductionsupporting
confidence: 83%
“…Water availability is thus the primary limiting factor, but when it becomes nonlimiting in case of favourable climate conditions (2013), then light becomes the next biggest limiting factor. Indeed, solar radiation appears to be an important environmental factor defining the regeneration niche of pine species: higher solar radiation implies higher seedling survival and higher initial seedling growth (Rodríguez-García et al 2011). Simard et al (1998) stated that increased light favours a longer taproot and longer shoots in seedlings, enabling them to penetrate the soil and survive better.…”
Section: Discussionmentioning
confidence: 99%
“…Kitzberger et al 2000;Gómez-Aparicio et al 2005;Howard et al 2012). Shrubs are also recognized as important niches for tree regeneration (Callaway 1995;Rodríguez-García et al 2011). The positive impact of one plant on another has been shown to occur by offering shading that helps improve microclimate (evapotranspiration lessening), increase nutrient availability and increase soil stability (see Callaway 1995 for a review).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations